2010
DOI: 10.3727/096368910x498250
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Rapid Labeling of Transplanted Cell Populations with Superparamagnetic Iron Oxide Nanoparticles Using Cell Surface Chemical Biotinylation for in Vivo Monitoring by MRI

Abstract: Determination of the dynamics of specific cell populations in vivo is essential for the development of cellbased therapies. For cell tracking by magnetic resonance imaging (MRI), cells need to internalize, or be surface labeled with a MRI contrast agent, such as superparamagnetic iron oxide nanoparticles (SPIOs): SPIOs give rise to signal loss by gradient-echo and T 2 -weighted MRI techniques. In this study, cancer cells were chemically tagged with biotin and then magnetically labeled with anti-biotin SPIOs. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 38 publications
0
17
0
1
Order By: Relevance
“…These results indicate that MIRB is biocompatible, and can be used for cell labeling and tracking for cell transplantation. With technological progress in nanotechnology, magnetic nanoparticles can be nontoxic, biocompatible and efficient for intracellular labeling [36,37] such as Feridex, an FDA approved contrast agent for MRI of adult patients to enhance the T2 weighted images used to detect and evaluate liver lesions [38]. However, limited MRI sensitivity cannot distinguish regenerative and differentiated cells from exogenous and endogenous transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that MIRB is biocompatible, and can be used for cell labeling and tracking for cell transplantation. With technological progress in nanotechnology, magnetic nanoparticles can be nontoxic, biocompatible and efficient for intracellular labeling [36,37] such as Feridex, an FDA approved contrast agent for MRI of adult patients to enhance the T2 weighted images used to detect and evaluate liver lesions [38]. However, limited MRI sensitivity cannot distinguish regenerative and differentiated cells from exogenous and endogenous transplanted cells.…”
Section: Discussionmentioning
confidence: 99%
“…Biotinylated peptides expressed on the plasma membrane were imaged with a contrast agent conjugated to streptavidin in rodent models 63, 64 . The human membrane-protein sodium-iodide symporter (NIS), responsible for iodide uptake in the thyroid, stomach, salivary gland and choroid plexus but minimally expressed elsewhere, was used to follow the survival and distribution of transplanted cells in pigs by hybrid SPECT/CT 32 .…”
Section: Cell Labelingmentioning
confidence: 99%
“…One method, magnetoporation, involves the coating of anionic SPIOs with cationic transfection agents such as protamine sulfate or poly-L-lysine 14. Stem cells subsequently endocytose the resulting complex during incubation for around 24-48 hours 15. Although many studies have shown that magnetoporation does not affect cell viability or function at low doses 15-17, there is evidence that high doses can inhibit mesenchymal stem cell (MSC) migration and colony formation ability 18.…”
Section: Direct Iron Particle Labelingmentioning
confidence: 99%
“…Stem cells subsequently endocytose the resulting complex during incubation for around 24-48 hours 15. Although many studies have shown that magnetoporation does not affect cell viability or function at low doses 15-17, there is evidence that high doses can inhibit mesenchymal stem cell (MSC) migration and colony formation ability 18. Another study showed inhibition of chondrogenesis in MSCs after FDA-approved Feridex labeling 19.…”
Section: Direct Iron Particle Labelingmentioning
confidence: 99%